SLAUGHTER AND MEAT QUALITY OF FATTENING PIGS FOR USE IN DIETS OF SOY PROTEIN CONCENTRATE DRY FEED - Скареднов, Д. Ю. (Scientific Progress & Innovations, 2013)
Given the results of studies of slaughter and meat quality of pigs fed on diets with differentGiven the results of studies of slaughter and meat quality of pigs fed on diets with differentprotein soy food production technologies: the pressure of expansion (concentrate dry soy protein food),spinning under pressure (soybean cake), Extrusion (extrudate soy). As a control sunflower oilcake. Found a significant positive effect of soy protein feed on growth rate, feed conversion, slaughterand meat quality of pigs, the morphological structure of the carcass. Best for slaughter yield carcasseswere fed to pigs counterparts cake and soy protein concentrate soy dry forage (+2.47% and 1.53%respectively to control). In general, meat and tallow products guinea pigs on key dimensions correspondto the normal categories of pork.